Keanekaragaman Jenis Tumbuhan Obat yang Dimanfaatkan oleh Pengobat Tradisional (Battra) Suku Dayak Mahap dan Suku Melayu di Desa Tembesuk Kabupaten Sekadau - Sofia Aliza Maharani; Gusti Eva Tavita; Fathul Yusro (Jurnal Serambi Engineering, 2021)
The Malays and the Dayak are the dominant tribes in West Kalimantan. Different tribes have different species of plants or the way they use medicinal plants. This study aims to analyze the type, processing method, and the use method of medicinal plants by traditional healers (Battra) from the Malay and Dayak Mahap tribes in Tembesuk village, Sekadau Regency. This study used a survey method, and the selection of respondents (Batrra) was carried out by purposive sampling technique. In Tembesuk Village, 8 Battra consist of 5 Malays and 3 Dayak Mahap people. The results showed that 80 species of plants were used by Batrra in Tembesuk village. Sixty species are distributed in the Malay tribe traditional healers, while the Dayak Mahap tribe traditional healers use 35 species. The plant part with the highest uses are leaves (60% of the Malays and 64.44% of the Dayak Mahap). The most common processing method is boiled (41.54% of the Malays and 41.18% of the Dayak Mahap), the way of use is drunk (35.82% of the Malays, and 41.18% Dayak Mahap). Most of the plants are wild (66.67% Malay and 58.33% Dayak Mahap), and the plant family with extensive use is Zingiberaceae (six plants in Malay and five in Dayak Mahap).